School culture, leadership, effectiveness and improvement, and student success in higher education - Baroud-Nabhani, Mona (2003)
The purpose of this study was to identify school factors that promoted students' academic and personal development and enhanced their success in higher education. The underlying assumption was that effective decentralised private schools have strong positive cultures, visionary leadership and adequate resources to remain effective and open to improvement. Five private secondary schools in Beirut were selected based on their reputation for decades of student success on national and university entrance examinations and achievement in private universities. Semi- structured interviews were conducted with principals, sample teachers, student groups, and alumni at a private university. Questionnaires were administered to the full-time teachers and simple frequency counts were used. School and classroom observations were conducted for two weeks in each school to examine daily manifestations of culture and effectiveness. School documents were analysed and data were crosschecked for triangulation. Criteria for university success were students' academic averages, years for graduation, participation in campus life, and interrelationships with faculty and friends (Koljatic and Kuh, 2001). Qualitative data analysis followed Cooper and McIntyre's (1996) method. Themes were reported using direct quotations in the narrative summary. The five self-managed schools determined their missions, student intake, standards, and reform. They have positive cultures and authentic visionary leaders who are culture promoters, instructional leaders, and disciplinarians. Leaders delegated responsibilities but ensured close coordination of programs and operations. A model of effective schools emerged. Two schools were identified as more effective than the others. Their practices reflected their missions, and their alumni were more involved in university life and interrelationships. This study validated the assumption that private schools prepare their students rigorously for academic and social success in higher education. It can serve as a model for school effectiveness